Optimization of Modern Style Marketing in the Era of Disruptive Technology at SME’s Batik New Normal Bogor - Fredi Andria; Anisa Intan Selatan; Soleha Nuramanah; Muhamad Sunarzi; Salmah Salmah; Amelia Rahmi; Eneng Tita Tosida; Abimanyu Okysaputra (Research Collaboration Community (RCC), 2022)
The purpose of this paper is to provide insight and understanding to the residents of Tegal Village, Kemang District, Bogor Regency, Indonesia, a good marketing pattern in marketing the products of the new normal Bogor batik village which is being developed. Furthermore, to optimize the implementation of marketing and digital marketing strategies by using the mineral style with the latest platforms. So that the ability of the marketing strategy of the new normal batik village business group can be boosted massively. The method used in this activity is classroom training to provide an initial understanding of theories and concepts, then practiced using participant gadgets in creating promotional digital accounts for each participant group representative. This program has clearly demonstrated an increase in the ability of the trainees to understand and apply their skills using current millennial-style marketing patterns. The target of the marketing strategy later, in addition to starting to try the application of digital marketing strategies, the participant group is taught to also continue to expand the market by using conventional strategies by involving related parties. In this case, the local government can be used as a target market for selling new normal batik products produced by the residents of Tegal Village in the future. The use of modern and millennial marketing styles, plus conventional market penetration, is expected to increase the ability of training participants, so that in due course of the new normal batik production process, these modern marketing patterns can boost sales and open wider market potential.